Analysing the Impact of Economic Growth on Forest Loss – The Moderating Role of Democratic Institutions - Cao, Kemiao (International Journal of Humanities and Social Science, 2025)
The purpose of this study is to explore the impact of economic growth on forest loss and to examine the moderating role of democratic institutions in it. Through panel data regression analysis, this paper analyses the effects of economic growth, institutional quality and their interaction on forest resource depletion in different countries. The results show that there is a significant negative correlation between economic growth and forest loss, i.e., economic growth is usually accompanied by forest resource depletion. At the same time, democratic institutions play a positive moderating role in this process. Specifically, democracies effectively mitigate the negative impacts of economic growth on forest resources by featuring higher policy transparency and public participation. The interaction effect analysis further proves that democratic institutions can play a key role in the process of economic growth and promote a balance between economic growth and environmental protection. Therefore, this paper suggests strengthening democratic governance, promoting green economic transformation, and enhancing international co-operation to promote sustainable development and forest resource conservation.